PENANAMAN SIKAP SOPAN-SANTUN PADA ANGGOTA IKATAN KELUARGA SILAT PUTRA INDONESIA (IKSPI) KERA SAKTI DI DESA SIDOMLANGEAN KECAMATAN KEDUNGPRING KABUPATEN LAMONGAN - Taibur Rachman; Listyaningsih - (Universitas Negeri Surabaya (Unesa), 2023)
The arrogance of youth who are members of the IKSPI Kera Sakti martial arts organization is very concerning, because they often commit acts that can harm the organization and damage the good name of IKSPI Kera Sakti. Fights with other martial arts organizations, drunkenness, behaving like a champ in the midst of community life to gambling and crime. This study aims to find out about the cultivation of good manners in members of the Indonesian Men's Silat Family Association (IKSPI) Kera Sakti in Sidomlangean Village, Kedungpring District, Lamongan Regency. The approach used in this study is a qualitative approach with data collection techniques in the form of participatory observation, interviews, documentation and data analysis. for the informants of this study, there were six people from one IKSPI Kera Sakti head of Sidomlangean Village, three senior trainers who had been members of IKSPI Kera Sakti for more than five years, and two students who were still practicing. Informants are determined using a purposive technique. The theory used in this research is Thomas Lickona's character education theory. In Thomas Lickona's theory of character education, there are three important elements, namely moral knowing, moral feeling, and moral behavior. The results of this study indicate that the inculcation of politeness in the IKSPI Kera Sakti organization in Sidomlangean Village was carried out by trainers during the training process, namely the first habit of shaking hands, praying and making student promises. Second, the development of knowledge about martial arts material. Third, practice the teachings of courtesy. The fourth award and punishment.